BALANCING WRITTEN AND AUDIO PEER FEEDBACK IN ACADEMIC WRITING: STUDENT EXPERIENCES WITH PADLET - Stojanovska-Ilievska, Natasha (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2025)
This article explores Macedonian university students’ reflections and preferences regarding online peer feedback in academic writing, with a focus on three key factors: the feedback mode (written vs. audio), the students’ role in the process (giver vs. recipient), and the writing task type (essay outline vs. fully developed draft). The study was conducted among second-year undergraduates enrolled in an academic writing course that integrated Padlet as a peer review platform. The data were collected through an online questionnaire that examined how students experienced giving and receiving feedback in both written and audio formats across different stages of writing. The study revealed that most students valued participating in feedback sessions across different modalities, although some of them reported feeling less confident when recording and posting their audio comments. Written feedback was preferred for the full drafts, while audio feedback was preferred for the essay outlines. The thematic analysis highlighted that written feedback was associated with comfort, easier navigation, and clarity, while audio feedback was valued for its spontaneity and the non-verbal communicative cues conveyed through the human voice. These findings underscore the importance of offering students diverse peer-review formats so as to encourage more effective peer feedback practices in academic writing instruction.